Oxidation of Perfumery Secondary Alcohols by Nicotinium Dichromate; A Kinetic Study: Life Sciences-Chemistry - Surulivel, C.; Dharmaraja, J.; Srinivasan, S.; Srinivasan, S. (International Journal of Life Science and Pharma Research, 2022)
Chemical kinetics is mainly concerned with studying the factors that change the reaction rate and the response mechanism. The present paper investigates the rate law for the reaction, order of the reaction of secondary alcohols(menthol) and compares it to other secondary alcohols like Borneol and Isoborneol. Diagnose the product of the oxidation reaction. The kinetics of oxidation of perfumery secondary alcohols [menthol], [Borneol], and [Isoborneol] by NDC have been studied in the aqueous acetic acid medium at 303K. The secondary perfumery alcohols were converted to the corresponding carbonyl compounds. The order concerning [Subs], [Oxi], and [H+] ions concentration is found to be one. The decrease in the dielectric constant of the medium enhances the rate of the reaction. The ionic strength of the medium has no significant effect on the reactivity of the response; it does not induce the polymerization of Acrylonitrile, indicating the absence of free radical pathway. The added Mn2+ ions show the reaction rate was slightly increasing order. The reaction has been studied at four different temperatures Eyring equation is used to calculate the thermodynamic parameters like Gibbs free energy change (ΔG#), entropy change (ΔS#), and enthalpy change (ΔH#). On increase in the temperature of the reaction, the rate of reaction increased abruptly. There was a decrease in entropy (ΔS#) of the system indicated by the value of entropy which showed some restriction in the freedom movement of the molecules. It was observed that the reactivity follows Menthol<Isoborneol<Borneol. Based on steric factors, structure, and isomeric characteristics of the alcohols under investigation.